2011
DOI: 10.1111/j.1460-9568.2011.07788.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous prolactin generated during peripheral inflammation contributes to thermal hyperalgesia

Abstract: Prolactin (PRL) is a hormone and a neuromodulator. PRL sensitizes TRPV1 responses in sensory neurons, but it is not clear whether peripheral inflammation results in the release of endogenous PRL, or whether endogenous PRL is capable of acting as an inflammatory mediator in a sex-dependent manner. To address these questions, we examined inflammation-induced release of endogenous PRL, and its regulation of thermal hyperalgesia in female and male rats. PRL is expressed in several types of peripheral neuronal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…PRL can modulate the function of CNS and PNS neurons, and it plays a critical role in diverse bodily functions such as maternal behavior (48), appetite (49), sexual receptivity (50), and hypersensitivity to painful stimuli (2)(3)(4), where the action of PRL on neurons can be either acute/transient or long term. Transient effects of PRL have been characterized in many neuronal types including gonadotropin-releasing hormone neurons, tuberoinfundibular dopamine neurons, the anteroventralperiventricular nucleus, and dorsal root ganglion and TG sensory neurons (2,7,17,51,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRL can modulate the function of CNS and PNS neurons, and it plays a critical role in diverse bodily functions such as maternal behavior (48), appetite (49), sexual receptivity (50), and hypersensitivity to painful stimuli (2)(3)(4), where the action of PRL on neurons can be either acute/transient or long term. Transient effects of PRL have been characterized in many neuronal types including gonadotropin-releasing hormone neurons, tuberoinfundibular dopamine neurons, the anteroventralperiventricular nucleus, and dorsal root ganglion and TG sensory neurons (2,7,17,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Because local trauma and inflammation lead to an increase in peripheral levels of PRL in female and to a lesser extent in male rats, it could be suggested that transient modulation of TRP channels by PRL in the periphery is one of underlying mechanisms for PRL-induced thermal (i.e. heat and cold) hyperalgesia (2)(3)(4). TRP channels are also involved in hypersensitivity to thermal and mechanical stimuli at presynaptic levels in the dorsal horn of the spinal cord and certain brain stem regions (62,63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In contrast to these chronic inflammatory conditions, acute inflammation does not cause elevated levels of PRL in blood. 29 The second pathological condition associated with elevated levels of PRL is physiological and physical stress (i.e., trauma). Burn, 30 surgical procedures, 31,32 associated with increased PRL serum levels.…”
Section: Prolactin In the Nervous Systemmentioning
confidence: 99%
“…7,29,[36][37][38][39][40] Dual regulation of extra-pituitary PRL by estrogen and pathological condition is not well studied. Therefore, direct measurements on alterations in PRL concentrations in relevant parts of the nervous system triggered by pathological conditions are important to consider.…”
Section: Prolactin In the Nervous Systemmentioning
confidence: 99%